Some newly recorded fishes from the magdalena river system (1945)
The following species, observed and collected in the course of a survey carried out for the Colombian Government, are recorded for the first time from the Magdalena drainage system. Specimens are in most cases preserved in the Museum of Fishes established in the offices of the Sección de Caza y Pesca of the Ministry of National Economy, Bogotá, and the numbers given are those recorded on the bottles kept at that institution.